Secrecy and Sustainability: How Concealment and Revelation Shape Vepsian Language Revival - Siragusa, Laura (Anthropologica, 2017)
In this article, I explore questions related to language sustainability, examining whether secrecy practices, both in written and oral form, support or hinder language revival. Within cultural anthropology, secrecy often reflects “epistemological and ethical dimensions” of the researcher and research institutions. The work presented in this article adds to this already-existing definition, providing an understanding of secrecy as an ontological practice. Stemming from fieldwork with Veps in northwestern Russia, this research demonstrates how secrecy fosters the sustainability of the Vepsian language, moving it from simply being used as a means for protecting and overcoming the challenges to Vepsian generational transmission. This change is reflected in the differences between literacy and orality.